Collaboration and Innovation Models in Information and Communication Creative Industries the Case of Germany - Stejskal, Jan; Hajek, Petr; Prokop, Viktor (Universiti Utara Malaysia Press, 2018)
In rapidly changing environment of global knowledge economy, innovations play an important role in the process of gaining competitive advantage. Specifically, information and communication creative industries are dependent on constant technological breakthroughs, new sources of knowledge and high innovativeness. Moreover, new knowledge and innovation outputs of these industries subsequently affect products and processes of other businesses as well as innovation activities within different industries. Knowledge acquisition, utilization and dissemination therefore represent important processes that significantly influence the firms´ innovation activities. It was proven that cooperation is an important determinant that helps to spread the existing knowledge and to create new knowledge through knowledge spillover effects. The paper deals with the determinants of cooperation and innovation to examine numerous effects on both activities in German information and communication creative industries. We also test the role of the determinants of innovation performance and their influence on the economic effect of innovation activities in terms of the percentage of innovative products in total turnover. For our analyses, we are using data from Community Innovation Survey 2008-2010. We empirically show that firms from German information and communication creative industries can create innovations through the collaboration and confirm that both internal and external communication significantly contribute to the creation of innovation. Moreover, we confirm the influence of internal expenditures on R&D and observe significant influence of external expenditures on R&D. In conclusion, we also provide some practical implications for policy makers.